The ever-dying people? : Canada's Jews in comparative perspective - Brym, Robert J., 1951-; Schnoor, Randal F. (University of Toronto Press, 2023)
"Demise by assimilation or antisemitism is often held to be the inevitable future of Jews in Canada and other diaspora countries. The Ever-Dying People? shows that the Jewish diaspora, while often held to be in decline, is influenced by a range of identifiable sociological and historical forces, some of which breathe life into Jewish communities, including Canada's. Bringing together leading Canadian and international scholars, The Ever-Dying People? provides a landmark report on Canadian Jewry based on recent surveys, censuses, and other contemporary data sources from Canada and around the world. This collection compares Canada's Jews with other Canadian ethnic and religious groups and with Jewish communities in other diaspora countries, including the United States, the United Kingdom, France, and Australia. It also sheds light on social divisions within Canadian Jewry: across cities, sub-ethnic groups, denominations, genders, economic strata, and political orientations. These bases of comparison usefully explain variation in a wide range of sociological phenomena, including ethnic identity, religiosity, acculturation, intermarriage, discrimination, economic achievement, and educational attainment."--